2015
DOI: 10.1177/0363546515618387
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Robotic Assessment of the Anterolateral Ligament, Part 1

Abstract: Residual internal rotation and a positive pivot shift after ACL reconstruction may be attributed to ALL injury. For these patients, surgical treatment of an ALL tear may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(102 citation statements)
references
References 34 publications
6
93
0
3
Order By: Relevance
“…18,27,34,36,42 Sonnery-Cottet et al 42 further demonstrated its significance in the presence of ACL injury. In their study, an isolated lesion of the ACL did not produce a pivot shift, which was instead only seen with a concurrent lesion of either the ALL or the ITB.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18,27,34,36,42 Sonnery-Cottet et al 42 further demonstrated its significance in the presence of ACL injury. In their study, an isolated lesion of the ACL did not produce a pivot shift, which was instead only seen with a concurrent lesion of either the ALL or the ITB.…”
Section: Discussionmentioning
confidence: 96%
“…In a separate investigation, in vitro robotic assessment of the ALL provided further evidence of its role in rotatory stability when subjected to a simulated pivot-shift test. 36 Through this same modality it was shown that a combined ACL/ALL reconstruction provided better rotatory control than an ACL reconstruction alone. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Despite these historical reports of the ALL, the most accurate anatomical description of the ALL has been provided by Claes et al [15], and its importance with regard to knee stability has been confirmed in numerous biomechanical studies [42, 53, 66, 71]. …”
Section: Historymentioning
confidence: 99%
“…The biomechanical properties of the ALL allow for internal rotation to be increased to over 30° of flexion; [71, 87] however, the pivot-shift seems to represent the most reliable test to evaluate ALL integrity. Monaco et al demonstrated that a grade III pivot shift is only seen in the absence of both the ACL and ALL in vitro [53].…”
Section: Clinical Diagnosismentioning
confidence: 99%
See 1 more Smart Citation